Engineering materials 1 : an introduction to properties, applications and design - Ashby, M. F.
"Widely adopted around the world, Engineering Materials 1 is a core materials science and engineering text for third- and fourth-year undergraduate students; it provides a broad introduction to the mechanical and environmental properties of materials used in a wide range of engineering applications. The text is deliberately concise, with each chapter designed to cover the content of one lecture. As in previous editions, chapters are arranged in groups dealing with particular classes of properties, each group covering property definitions, measurement, underlying principles, and materials selection techniques. Every group concludes with a chapter of case studies that demonstrate practical engineering problems involving materials."--pub. desc.